Ten-year all-cause mortality according to smoking status in patients with severe coronary artery disease undergoing surgical or percutaneous revascularization. (30th November 2020) - Takahashi, Kuniaki; Thuijs, Daniel J F M; Gao, Chao; Ono, Masafumi; Holmes, David R; Mack, Michael J; Morice, Marie-Claude; Mohr, Friedrich-Wilhelm; Curzen, Nick; Davierwala, Piroze M; Milojevic, Milan; Dawkins, Keith D; et al.
Abstract: Aims: To evaluate the impact of various smoking status on 10-year all-cause mortality and to examine a relative treatment benefit of coronary artery bypass grafting (CABG) vs. percutaneous coronary intervention (PCI) according to smoking habits. Methods and results: The SYNTAX Extended Survival study evaluated vital status up to 10 years in 1800 patients with de novo three-vessel disease and/or left main coronary artery disease randomized to CABG or PCI in the SYNTAX trial. In the present analysis, patients were divided into three groups (current, former, or never smokers), and the primary endpoint of 10-year all-cause mortality was assessed according to smoking status. Smoking status was available in 1793 (99.6%) patients at the time of randomization, of whom 363 were current smokers, 798 were former smokers, and 632 were never smokers. The crude rates of 10-year all-cause mortality were 29.7% in current smokers, 25.3% in former smokers, and 25.9% in never smokers (Log-rank P = 0.343). After adjustment for imbalances in baseline characteristics, current smokers had a significantly higher risk of 10-year all-cause mortality than never smokers [adjusted hazard ratio (aHR): 2.29; 95% confidence interval (CI): 1.60–3.27; P < 0.001], whereas former smokers did not. PCI was associated with a higher risk of all-cause mortality than CABG among current smokers (HR: 1.60; 95% CI: 1.09–2.35; P = 0.017), but it failed to show a significant interaction between revascularization strategies and smoking status ( P interaction = 0.910). Conclusion: Current smokers had a higher adjusted risk of 10-year all-cause mortality, whereas former smokers did not. The treatment effect of CABG vs. PCI did not differ significantly according to smoking status. Clinical trial registration: SYNTAX: ClinicalTrials.gov reference: NCT00114972; SYNTAX Extended Survival. ClinicalTrials.gov reference: NCT03417050.